Exploring the active ingredients and potential mechanisms of Pingchan granules in Parkinson’s disease treatment through network pharmacology and transcriptomics - Qiu-Han Xu; Yi-Ling Wang; Cheng Wang; Si-Si Jiang; Bao-Rong Zhang; Jun Tian (Scientific Reports)
Abstract Parkinson’s disease (PD), the second most prevalent neurodegenerative disorder, poses significant challenges to single-target therapeutic strategies due to its complex etiology. This has driven interest in multi-target approaches, particularly those leveraging natural compounds. Pingchan granules (PCG), a traditional Chinese medicine composed of plant- and animal-derived compounds, have shown efficacy in alleviating PD symptoms. Here, we identify 96 PCG-associated anti-PD targets, enriched in neuronal synaptic signaling and G protein-coupled receptor pathways. Through protein-protein interaction network analysis of anti-PD targets and random forest modeling of substantia nigra transcriptomic data from PD patients, SLC6A3 and SRC emerged as central hub targets, with Mendelian randomization further validating SRC as a potential therapeutic target. Molecular docking and single-cell sequencing reveal that dauricine, PCG’s principal active compound, binds strongly to SLC6A3 and SRC, modulating glucose metabolism pathways in dopaminergic neurons. These findings illuminate the molecular basis of PCG’s therapeutic effects, offer a foundation for future drug development, and underscore the potential of dauricine as a targeted treatment for PD.